Feasibility of the Epiduroscopy Simulator as a Training Tool: A Pilot Study - Jong Joo Lee; Junho Ko; Yeomin Yun; Seong-Wook Jang; Yoon Ha; Yoon Sang Kim; Dong Ah Shin (Pain Research and Management)
Epiduroscopy is a type of spinal intervention that visualizes the epidural space through the sacral hiatus using a fiberoptic scope. However, it is technically difficult to perform compared to conventional interventions and susceptible to complications. Surgery simulator has been shown to be a promising modality for medical education. To develop the epiduroscopy simulator and prove its usefulness for epiduroscopy training, we performed a case-control study including a total of 20 physicians. The participants were classified as the expert group with more than 30 epiduroscopy experiences and the beginner group with less experience. A virtual simulator (EpiduroSIM™, BioComputing Lab, KOREATECH, Cheonan, Republic of Korea) for epiduroscopy was developed by the authors. The performance of the participants was measured by three items: time to reach a virtual target, training score, and number of times the dura and nerve are violated. The training score was better in the expert group (75.00 vs. 67.50; P<0.01). The number of violations was lower in the expert group (3.50 vs. 4.0; P<0.01). The realism of the epidural simulator was evaluated to be acceptable in 40%. Participants improved their simulator skills through repeated attempts. The epiduroscopy simulator helped participants understand the anatomical structure and actual epiduroscopy.